2014
DOI: 10.1021/ef5015549
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electron Spin Resonance Study of Molecular Dynamics of Asphaltenes at Elevated Temperature and Pressure

Abstract: A comparison of the behavior of asphaltene molecules extracted from crude oil and dissolved in aromatic solvent as a model system with the behavior of vanadium-containing molecules in real crude oils via ESR in-situ technique showed that the changes of rotational mobility of asphaltene molecules can be related to the changes of the local viscosity and environment of the asphaltenes as well as the characteristic sizes of vanadyl-containing fragments due to aggregation/disaggregation processes in crude oils. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…There has been an inspiring research in paramagnetic centers of petroleum derivatives for last five years by EPR and ESR, especially for vanadyl porphyrin (VO 2 + ). The high sensitivity of EPR and ESR could detect low concentrations of vanadium species in asphaltenes, provide in situ information of sizes of vanadium molecules and their aggregates, distinguish different types of environments of vanadium species, and monitor environmental dynamics [31,[149][150][151] . The mechanisms of hydrodemetallization were also investigated using EPR [149,152] .…”
Section: Electron Paramagnetic Resonance (Epr) and Electron Spin Resomentioning
confidence: 99%
“…There has been an inspiring research in paramagnetic centers of petroleum derivatives for last five years by EPR and ESR, especially for vanadyl porphyrin (VO 2 + ). The high sensitivity of EPR and ESR could detect low concentrations of vanadium species in asphaltenes, provide in situ information of sizes of vanadium molecules and their aggregates, distinguish different types of environments of vanadium species, and monitor environmental dynamics [31,[149][150][151] . The mechanisms of hydrodemetallization were also investigated using EPR [149,152] .…”
Section: Electron Paramagnetic Resonance (Epr) and Electron Spin Resomentioning
confidence: 99%
“…Different aspects of application of various electron paramagnetic resonance (EPR) and double resonance (ENDOR) techniques for the elucidation of the asphaltene architecture and the oil PC nature are covered in refs. [2,19,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the use of the VP as a native probe for the investigation of asphaltenes is determined by the resolved anisotropic spectral parameters (g-factor and hyperfine components, zero-field splitting, quadrupole tensors) in the EPR/ENDOR spectra, which makes VP to be orientationselective even in disordered media [40][41][42][43][44][45][46][47][48][49][50][51]. Using X-band (microwave frequency ν MW of 9 GHz, magnetic field B 0 of 0.34 T) and high-frequency (ν MW of 95 GHz, B 0 of 3.4 T, W-band) conventional and pulsed EPR/ENDOR techniques, we have shown that, on the one hand, the EPR and ENDOR spectra for VP in the initial oil samples of different genesis are similar while, on other hand, the relaxation parameters of VP (the electron longitudinal (T 1e ) and transverse (T 2e ) relaxation times) and the temperature dependences of the EPR spectra depend strongly on the nature of the sample and the method of the fractionation procedure [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…To study the concentrates of oil metal porphyrins other methods can be used, such as EPR spectroscopy [14,15], LDI mass-spectrometry [16], Fourier transform ion cyclotron resonance mass spectrometry [17], and high definition inductively coupled plasma mass spectrometry [18].…”
Section: Introductionmentioning
confidence: 99%